$\estwo{y = \exponential{x}{3} - 12 x + 8}{x = -3} $

Solve for y, x

x=-3

y=17

Graph

## Share

Copied to clipboard

y=\left(-3\right)^{3}-12\left(-3\right)+8

Consider the first equation. Insert the known values of variables into the equation.

y=-27-12\left(-3\right)+8

Calculate -3 to the power of 3 and get -27.

y=-27+36+8

Multiply -12 and -3 to get 36.

y=9+8

Add -27 and 36 to get 9.

y=17

Add 9 and 8 to get 17.

y=17 x=-3

The system is now solved.

## Examples

Quadratic equation

{ x } ^ { 2 } - 4 x - 5 = 0

Trigonometry

4 \sin \theta \cos \theta = 2 \sin \theta

Linear equation

y = 3x + 4

Arithmetic

699 * 533

Matrix

\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]

Simultaneous equation

\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.

Differentiation

\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }

Integration

\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x

Limits

\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}